Effectiveness of Inquiry and Evidence-based Pedagogies on Achievement, Retention, and 21st-Century Skills of Marketing Students in Nigeria - Ekahe Abanyam, Friday; Atah Abanyam, Victor; Ngozi Ibelegbu, Anthonia; Okosun Odozua, Loveth (Journal of Pedagogy and Education Science, 2025)
In today's professional world, mastering both 21st-century skills and technical expertise is crucial for career success. Therefore, educators, especially in Digital Marketing, are urged to adopt progressive teaching methods to facilitate skill acquisition among students. With this goal in mind, we examined the impact of inquiry and evidence-based teaching on academic achievement, retention rates, and the development of 21st-century competencies in marketing students. Using the Solomon Four design, we divided 260 students into four intact classes and conducted pre-test and post-test evaluations. Statistical analyses employing MANOVA and ANCOVA revealed significant improvements in academic achievement, retention rates, and the cultivation of 21st-century competencies among students in the experimental groups compared to those in the control groups. The findings demonstrated substantial advancements in academic knowledge retention and the acquisition of 21st-century competencies among students in the experimental groups, particularly through inquiry and evidence-based pedagogies, which outperformed traditional lecture-based approaches. While differences between the inquiry and evidence-based cohorts were minimal, both significantly surpassed the performance of lecture-based instruction. Moreover, both inquiry and evidence-based approaches facilitated the development of critical, analytical, innovative, and collaborative skills among students. Notably, male students made greater progress in critical and analytical thinking, while females showed slightly stronger collaborative abilities. In conclusion, this study emphasized innovative pedagogies for effectiveness in boosting academic performance, retention, and 21st-century skills among marketing students. Gender and age minimally impact outcomes, emphasizing the superiority of inquiry and evidence-based methods over traditional lecture-based instruction in marketing education.